2016
DOI: 10.1111/cpf.12347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of guided breath exercise on complex behaviour of heart rate dynamics

Abstract: Guided breath exercises acutely increased chaotic behaviour of HRV measured by HFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
2
19
0
4
Order By: Relevance
“…According to our findings, studies comparing controlled and spontaneous breathing rhythm conditions reported significant changes in all HRV domains (Barth & Vecchio, ; Tavareset al, ). These findings suggest that if breathing rate control is adopted during a baseline rest record, the values obtained will already be influenced by a variable that may change the HRV values, compromising the investigation of other variables that would have the potential to change the HRV indices.…”
Section: Discussionsupporting
confidence: 78%
“…According to our findings, studies comparing controlled and spontaneous breathing rhythm conditions reported significant changes in all HRV domains (Barth & Vecchio, ; Tavareset al, ). These findings suggest that if breathing rate control is adopted during a baseline rest record, the values obtained will already be influenced by a variable that may change the HRV values, compromising the investigation of other variables that would have the potential to change the HRV indices.…”
Section: Discussionsupporting
confidence: 78%
“…Similar results are reported by Critchley et al ( 2015 ) study on hypoxia. Many other studies show that slow and diaphragmatic breathing increases PNS activity, as measured by blood pressure, heart rate or heart rate variability (HRV; Hirsch and Bishop, 1981 ; Lee et al, 2003 ; Pal et al, 2004 ; Lehrer and Gevirtz, 2014 ; Van Diest et al, 2014 ; Mortola et al, 2015 ; Perciavalle et al, 2017 ; Tavares et al, 2017 ; for some conflicting results see and Montgomery, 1994 ; Conrad et al, 2007 ). In sum, experimental slowing of respiration seems to shift the balance between SNS and PNS activity towards the latter.…”
Section: Effective Factors In Contactsmentioning
confidence: 99%
“…Most experimental studies show higher HRV following breathing instructions, consistent with the involvement of rVNS. In particular, there is ample evidence that slow and deep breathing increase HRV indices of vagal tone (Hirsch and Bishop, 1981 ; Pal et al, 2004 ; Larsen et al, 2010 ; Lehrer and Gevirtz, 2014 ; Critchley et al, 2015 ; Mortola et al, 2015 ; Tavares et al, 2017 ) and lowers stress markers such as: heart rate, blood pressure and salivary cortisol (Lee et al, 2003 ; Pramanik et al, 2009 ; Perciavalle et al, 2017 ). Van Diest et al ( 2014 ) looked specifically at the effects of different inhalation/exhalation ratio at either slow or normal respiration rate on different HRV measures (peak-valley, HF): higher HRV (both measures) was reported in the slow respiration condition, but only for extended exhalation, inhalation/exhalation ratio: 0.24, and not for extended inhalation, inhalation/exhalation ratio: 2.33.…”
Section: The Respiratory Vagal Stimulation Model Of Contemplative Actmentioning
confidence: 99%
“…In the majority of researches authors hold the opinion concerning importance of training of the person in full breath and its any regulation (Szabo & Kocsis, 2017;Tavares, de Paula Vidigal, Garner, de Abreu, & Valenti, 2017;Cernes & Zimlichman, 2017;Todd, Walsted, Grillo, Menzies-Gow, & Hull, 2018). At the same time in special literature, there are a large number of results of the experimental studies demonstrating the advantage of a hypoxia .…”
Section: Discussionmentioning
confidence: 99%